Multi isotope systematics of precipitation to trace the sources of air pollutants in Seoul, Korea. (1st October 2021) - Kim, Yeongmin; Lee, Insung; Farquhar, James; Kang, Jisuk; Villa, Igor M.; Kim, Hyoungbum
Abstract: Multiple sulfur (δ 34 Ssulfate, Δ 33 Ssulfate, & Δ 36 Ssulfate ), nitrogen and oxygen (δ 15 Nnitrate & δ 18 Onitrate ) and strontium ( 87 Sr/ 86 Sr) isotope compositions of precipitation collected from Seoul, South Korea were analyzed to study the sources, transportation and deposition of air pollutants in East Asia. The δ 34 Ssulfate values (from 1.9 to 14.6‰ with a median of 4.7‰) and the δ 15 Nnitrate values (from −2.0 to 13.3‰ with a median of 1.0‰) suggest that fossil fuel use (emission from coal combustion and vehicle exhaust) is a predominant source for sulfur and nitrogen, but other natural sources including biogenic contributions of DMS also add to their total budget. The seasonal variations are observed in δ 34 Ssulfate and δ 15 Nnitrate values (both higher in winter season), which is likely to result from the increase of coal use for domestic heating in China. The δ 18 Onitrate values also varied seasonally depending on the NOx oxidation pathway, being about 20‰ higher in winter than in summer season. The Δ 33 Ssulfate and Δ 36 Ssulfate values are not anomalous, showing the absence of MIF signals in precipitation of Seoul. The 87 Sr/ 86 Sr ratio of the precipitation samples range from 0.70988 to 0.71487 with a median of 0.71073, indicating the influence of at least three end-member (silicate dust, carbonate dust and anthropogenic emission). Ionic ratios such as (K + +NH4 + )/(Ca 2+ +Mg 2+ ) and Cl − /Na + suggest the overwhelming effect of anthropogenic input rather than carbonate dust on the end-member with lower 87 Sr/ 86 Sr ratios. Graphical abstract: Image 1 Highlights: Multi isotope systematics (N, O, S and Sr) of precipitation in Seoul are examined. We investigated sources, migration and deposition of air pollutants in East Asia. Fossil fuel use is the most predominant source for sulfur and nitrogen. Seasonal variations of δ 34 Ssulfate, δ 15 Nnitrate & δ 18 Onitrate are observed. Multiple sources affect the isotopic composition of precipitation in Seoul.